Mapping with Words : Anglo-Canadian Literary Cartographies, 1789-1916 - Krotz, Sarah Wylie, 1977− (Book collections on Project MUSE., 2018)
Mapping with Words re-conceptualizes settler writing as literary cartography. The topographical descriptions of early Canadian settler writers generated not only picturesque and sublime landscapes, but also verbal maps. These worked to orient readers, reinforcing and expanding the cartographic order of the emerging colonial dominion. Drawing upon the work of critical and cultural geographers as well as literary theorists, Sarah Wylie Krotz opens up important aesthetic and political dimensions of both familiar and obscure texts from the nineteenth century, including Thomas Cary's Abram's Plains, George Monro Grant's Ocean to Ocean, and Susanna Moodie's Roughing it in the Bush. Highlighting the complex territoriality that emerges from their cartographic aesthetics, Krotz offers fresh readings of these texts, illuminating their role in an emerging spatial imaginary that was at once deeply invested in the production of colonial spaces and at the same time enmeshed in the realities of confronting Indigenous sovereignties.